The Effect of Technological Innovation and Knowledge Management Process on Organisational Agility: A Systematic Literature Review - Alkaabi, Saleh Mohammed Yousef Obaid; Sohaimi, Nor Suzylah Binti; Bin Yatiban, Aminurraasyid (Engineering, Technology & Applied Science Research, 2024)
Organizational agility has become essential and its importance has increased after COVID-19. There are inconsistent findings regarding the factors that affect organizational agility. This study focuses on the effect of technological innovation and the knowledge management process by reviewing the literature related to these variables. Three databases, Scopus, Web of Science (WoS), and Google Scholar, were used using certain search keywords, and a total of 30 articles were identified between 2010 and 2022 and reviewed. The findings showed that the number of articles has increased sharply during and after the COVID-19 pandemic. However, the use of theories to explain organizational agility is still emerging, with the resource-based view, the dynamic capability, and the knowledge-based view being the most used theories. The sample size is increasing to meet the structural equation modeling requirements. The effect of technological innovation and the knowledge management process is positive in most studies. More studies are needed to examine organizational agility as a dependent variable in different countries, contexts, and industries. In addition, future studies should examine other moderating variables in this context.